(untitled) (Journal of the College of Basic Education, 2022)
The Sovereign Council was formed to undertake responsibilities of the president .and a senior officer Mohammed Najeeb Al-Rubaiee was chosen to be its chairman , but there was no real authority of this council . Before the members of Sovereign Council start the activities ,a presidential decree was issued under No ( 1 ) in the name of Sovereign Council confined all military and civil powers under the control of Abdulkareen Qasim and Abdulsalam Mohammed Arif . Therefore; all statements and decrees issued by Abdul Karen Qasim as issued by Sovereign Council . It was scheduled for the Sovereign Council to practice powders of the president . Regarding minister’s council . it was decided to practice both legislative and executive powers .It is not fair to criticize the leader Abdulkareen Qasim as the dignitaries members of Sovereign Council were not elected by people , but the leader chose them because they represented the largest possible numbers of Iraq political trends in the government , besides the changing in the power was due to armed revolutionary lead by the army and if there was free election , then no need to the revolution at all .